Pengaruh Metode Demonstrasi terhadap Dribbling Zig-Zag Sepak Bola Siswa SD - Heka Maya Sari Br Sembiring; Joen Parningotan Purba; Rizki Bastanta B. Manalu; Rahul Pandiangan (Jurnal Pendidikan, Media, Strategi, dan Metode., 2026)
This study aims to determine the effect of the demonstration method on elementary school students' zig-zag football dribbling skills at UPT SD Negeri 060972 in the 2025/2026 academic year. The study employed a quantitative experimental approach using a pre-experimental one group pretest-posttest design. The population and sample consisted of all 21 first-grade students of UPT SD Negeri 060972 selected through total sampling. The research instrument was a zig-zag football dribbling skill test administered before and after six meetings of instruction using the demonstration method. The data were analyzed using descriptive statistics, the Shapiro-Wilk normality test, homogeneity test, and paired sample t-test with IBM SPSS Statistics version 25 at a significance level of 0.05. The findings show that the mean dribbling completion time decreased from 18.22 seconds in the pretest to 15.44 seconds in the posttest, indicating an improvement of 2.78 seconds. The pretest and posttest data were normally distributed, with significance values of 0.561 and 0.754, and homogeneous with a significance value of 0.417. The paired sample t-test showed t = 18.567 with a significance value of 0.000. Therefore, the demonstration method has a significant effect on improving elementary students' zig-zag football dribbling skills and can be used as an effective alternative strategy in physical education learning.